(untitled) (Research, Society and Development, 2024)
Endocryne disruptors are chemical substances capable of interfering with hormonal homeostasis, altering synthesis, function, storage and/or metabolism of hormones, so that they can influence several aspects of female health by interfering with the endocrine system. Objective: to analyse the effects of endocrine disruptors on female reproductive health. Methodology: This study was carried out by bibliographic review of literature. Scientific documents and official documents of National and International Health Organizations have been used and the work published in the last 10 years (2014-2024) has been selected in Portuguese and English languages. The research databases were SCIELO, PUBMED and EBSCO. Discussion: exposure to endocrine disruptors in women aged 45 to 55 shows strongly an association with the earliest menopause, occurring from 1.9 to 3.8 years earlier, when there are increased serial or urinary levels of endocrine disruptors. There is an increased prevalence association of SOP (polycystic ovaries syndrome) in reproductive age when subjected to the largest exposure of per and polyfluoroalkyl (PFAS) and bisphenol A (BPA). Several classes of endocrine disruptors are associated with endometriosis, female infertility, and premature ovarian insufficiency. Final considerations: human exposure to endocrine disruptor chemicals is permanent and continuous, as they are present in various daily products. This leads to disruption in female reproductive health, and the nutritionist’s role of guiding how to minimise exposure and above all to encourage a healthier lifestyle.